Evaluation of the intratidal compliance profile at different PEEP levels in children with healthy lungs: a prospective, crossover study. (November 2020) - Lee, Ji-Hyun; Ji, Sang-Hwan; Lee, Hyung-Chul; Jang, Young-Eun; Kim, Eun-Hee; Kim, Hee-Soo; Kim, Jin-Tae
Abstract: Background: Optimal intraoperative lung protective ventilation (LPV) strategies in young children are largely under-explored. Individualised PEEP levels are likely to contribute to optimal lung protection. We determined optimal PEEP levels in young children during general anaesthesia by evaluating changes in intratidal compliance with varying PEEP. Methods: Children aged ≤6 yr were enrolled in this prospective interventional study. After induction of general anaesthesia and neuromuscular block (rocuronium), children were randomly assigned to be mechanically ventilated at each of three PEEP levels for 15 min each: 5, 8, and 12 cm H2 O PEEP (PEEP5/8/12 ). Haemodynamic and respiratory data were recorded at each PEEP level. Intratidal volume-compliance was classified into one of six compliance profiles (increasing/decreasing/horizontal [plateau]/increasing-horizontal/horizontal-decreasing/increasing-horizontal-decreasing) at each PEEP level. The primary outcome was intratidal compliance at different PEEP levels. Results: Forty-seven children were enrolled (40% female; median age: 2.5 yr [0.9–3.7]). Mean airway pressure progressively increased from 7.6 cm H2 O (0.5) at PEEP5, 10.5 cm H2 O (0.9) at PEEP8 to 14.3 cm H2 O (0.5) PEEP12 ( P <0.001). Mean driving pressure was lower at PEEP12 (6.3 cm H2 O [1.1]), compared with PEEP8 (6.5 cm H2 O [1.1]) and PEEP5 (7.0 cm H2 O [1.5]; P =0.004 for trend). Intratidal compliance increased in 31/47 (66%) children at PEEP5, but was less likely with PEEP8 (9/47; 19.1%) and was absent at PEEP12 . At PEEP8, plateaued compliance was most frequent (16/46; 34.8%). At PEEP12, decreasing compliance occurred most frequently (32/46; 69.6%). Conclusions: Intratidal compliance at different PEEP levels varied widely in young children under general anaesthesia. These data suggest that individualised PEEP levels are required for optimal lung protection in children. Clinical trial registration: NCT03533296 .